Social change Metropolitan community - Duncan, Dudley Otis (New York Russell Sage Foundation, 1973)
Describes a metropolitan community, explains how one comes into being and discusses the people, way of life, government, and problems of a city.
Keywords: Cities and towns -- Juvenile literature; Cities and towns; Metropolitan areas; Social sciences